Hubungan Dukungan Informasi Orang Tua Dan Teman Sebaya Dengan Pengetahuan Remaja Tentang Pencegahan HIV/AIDS di SMA Negeri 1 Tawangsari - Utomo, Hasbi Dwi; Kusumaningrum, Tanjung Anitasari Indah (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Background: Parents and peers are very important in providing information about HIV/AIDS as an effort to prevent HIV/AIDS transmission. Objective: This study aims to analyze the relationship between parental and peer information support and adolescent knowledge about HIV/AIDS prevention in SMA Negeri 1 Tawangsari. Methods: This type of research is analytic observational with a cross-sectional approach. This research was conducted in Tawangsari District, Sukoharjo with 218 students as respondents and the respondents were taken using proportional random sampling. The data collection technique in this study was using a questionnaire filled out by respondents offline. Results: The results showed that there was no relationship between parental information support (p> 0.783), and peer information support (p> 0.741) with adolescent students' knowledge of HIV/AIDS prevention at SMA Negeri 1 Tawangsari. Conclusion: There is no relationship between parental and peer information support and adolescent knowledge about HIV/AIDS prevention at SMA Negeri 1 Tawangsari. Suggestion: Parents and peers are expected to be able to provide information about VCT related to adolescent knowledge about HIV/AIDS prevention. Keywords: Adolescent knowledge, HIV/AIDS prevention